2019
DOI: 10.3389/fpsyg.2019.02847
|View full text |Cite
|
Sign up to set email alerts
|

Physical Couple and Family Violence Among Clients Seeking Therapy: Identifiers and Predictors

Abstract: Introduction: Couple violence (CV) affects many, and the consequences of those actions are grave, not only for the individual suffering at the hand of the perpetrator but also for the other persons in the family. Violence often happens among more than just the adults within one family. Even if CV has been thoroughly investigated in the general population very few studies have investigated this objective on a clinical sample, and none of these have included family violence. Aim: This article identifies and desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…This finding is in line with Gausel and Leach (2011) argument that the threat to the social-image is a motivator of anti-social responses and hostility. Moreover, this finding bears resemblance to Zahl-Olsen et al (2019) findings where anger and violence in families seems to be fueled by rejecting criticism for failure. It also lends support to Gausel et al (2018) findings that victims of failures reacted with hostile anger toward others due to the fears that their social-image would be damaged.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This finding is in line with Gausel and Leach (2011) argument that the threat to the social-image is a motivator of anti-social responses and hostility. Moreover, this finding bears resemblance to Zahl-Olsen et al (2019) findings where anger and violence in families seems to be fueled by rejecting criticism for failure. It also lends support to Gausel et al (2018) findings that victims of failures reacted with hostile anger toward others due to the fears that their social-image would be damaged.…”
Section: Discussionsupporting
confidence: 76%
“…If such a threat to the social-image is appraised, people often react with anger directed at the others that can possibly come to condemn them for their failure ( Gausel, 2013 ). In empirical support of this, a recent study on family therapy and reciprocal partner-violence, Zahl-Olsen et al (2019) found that outburst of anger and violence toward the other was associated with appraised condemnation manifested through rejecting behavior from the other as well as criticism for failure. Gausel et al (2018) found that the more victims of immorality feared that they would be condemned for their own perpetrating failures in a reciprocal conflict, the more they reacted with hostile anger toward others.…”
Section: Introductionmentioning
confidence: 88%
“…If such a threat to the social-image is appraised, people often react with anger directed at the others that can possibly come to condemn them for their failure (Gausel, 2013). In empirical support of this, a recent study on family therapy and reciprocal partnerviolence, Zahl-Olsen et al (2019) found that outburst of anger and violence toward the other was associated with appraised condemnation manifested through rejecting behavior from the other as well as criticism for failure. Gausel et al (2018) found that the more victims of immorality feared that they would be condemned for their own perpetrating failures in a reciprocal conflict, the more they reacted with hostile anger toward others.…”
Section: Vocational Education: Dropping Outmentioning
confidence: 87%
“…Consequently, physical and mental health can also have a lasting effect even after the violence has stopped [3]. Partner violence is one of the most painful and traumatic experiences because it destroys interpersonal trust and a sense of security [4]. DV that often occurs in adolescents usually in the form of physical, economic, psychological, mental, and sexual violence.…”
Section: Introductionmentioning
confidence: 99%